Mathematical Communication Skills of Junior High School Students in Solving Straight Line Equation Problems Based on Learning Interest - Abdul Ghany, Willy; Cahya M, Endang; Juandi, Dadang (KnE Social Sciences, 2024)
One of the skills that students should possess to compete in the 21st century is communication skills, including mathematical communication skills. In short, mathematical communication skill is an ability of students to convey their mathematical ideas. However, the facts show that the mathematical communication skills of junior high school students are still relatively low. This problem is closely related to learning interests. This study aims to analyze and describe the mathematical communication skills of junior high school students in solving straight-line equation problems based on learning interest. This study used a qualitative research method with a case study design. The research subjects were 33 grade VIII students from one of the junior high schools in Bandung, West Java, Indonesia. Data were collected using triangulation techniques from data on mathematical communication skills tests about straight line equations, learning interest questionnaires, and interviews. The research findings revealed that students with good and very good learning interests, mostly at level 3 mathematical communication skills (in general they can communicate ideas effectively but there are some small errors), students in the good enough learning interest category are at level 2 mathematical communication skills (can communicate some ideas with slightly ambiguous explanations), and students in poor learning interest are at level 3 mathematical communication skills (in general they can communicate ideas effectively but there are some minor errors). Keywords: mathematical communication,students, straight line equations, learning interest